Methylene blue dye as a single tracer for sentinel lymph node biopsy in early breast cancer - Patil, Vishwanath; Agarwal, Garima; Gupta, Shalu; Thobbi, Raksha R.; Shettigar, Sandesh; Agarwal, Ayushi; Goyal, Anushka (International Journal of Research in Medical Sciences, 2026)
Background: Sentinel lymph node biopsy (SLNB) can reduce the morbidity of axillary lymph node dissection (ALND) in clinically node-negative breast cancer, but dual-tracer SLNB requires nuclear medicine infrastructure that is unavailable in many Indian hospitals. We evaluated 1% methylene blue dye (MBD) as a single tracer for SLNB in a resource-constrained setting. Methods: In this prospective observational study, 30 women with clinically node-negative, early-stage breast cancer (T1-T2, N0, M0) underwent periareolar injection of 3 ml of 1% MBD during modified radical mastectomy. Sentinel lymph node(s) were identified and harvested separately during axillary dissection, followed by complete axillary lymph node dissection in all patients during our unit’s learning phase for histopathological validation. Results: A sentinel node was identified in 29 of 30 patients (96.67%). Among these 29 patients, sensitivity was 88.89%, specificity 95.00%, positive predictive value 88.89%, negative predictive value 95.00%, and overall accuracy 93.10%. The false-negative rate was 11.11%. No anaphylaxis, skin necrosis, allergic reaction, or wound complication occurred. Three patients (10.0%) developed transient skin tattooing that resolved spontaneously. Conclusions: MBD-only SLNB achieved a high identification rate and diagnostic accuracy during the learning phase, with no major adverse events. It may provide a pragmatic, low-cost alternative for axillary staging where radioisotope-based SLNB is unavailable. Larger multicentre studies are required before ALND can be safely omitted after a negative MBD-only SLNB.